Reaching the Mountaintop: Addressing the Common Core Standards in Mathematics for Students with Mathematics Difficulties. Issue 1 (18th February 2013) - Powell, Sarah R.; Fuchs, Lynn S.; Fuchs, Doug
<x xml:space="preserve">Abstract</x> The Common Core State Standards provide teachers with a framework of necessary mathematics skills across grades K‐12, which vary considerably from previous mathematics standards. In this article, we discuss concerns about the implications of the Common Core for students with mathematics difficulties (MD), given that students with MD, by definition, struggle with mathematical skills. We suggest that instruction centered on the Common Core will be challenging and may lead to problematic outcomes for this population. We propose that working on foundational skills related to the Common Core standards is a necessary component of mathematics instruction for students with MD, and we provide teachers with a framework for working on foundational skills concurrent with the Common Core standards. We caution, however, that implementation of the Common Core is in its infancy, and the implications of the Common Core for students with MD need to be monitored carefully.